Sofrimento e Adaptação: Aspectos Sociais e Psico-afetivos de Pacientes com Doença Periodontal Crônica - Denari, Ewa Danuta Cichecka (2004)
The purpose of this study was to characterize the patients from a clinic of a dentistry school; to investigate psychological and affectivity aspects related to periodontal diseases in those patients, besides the defensive resources they use. Method: social and demographical basis as well as general and periodontal health information of 789 patients looked after at a clinic of a dentistry school were picked up, which composed the quantitative stage of the study. This characterization was done throughout planning board specially worked out for the research. From those planning board on, another sample were selected by 273 patients who were denominated multi-complainant as they complained of three or more organic systems besides the periodontal complaint. A third sample was composed by 59 multi-complainant patients diagnosed with mild to moderate or mild to severe periodontal disease. Three of those patients were interviewed who composed the qualitative stage of the research. The results showed that among multi-complainant patients there were no significant association of mild to moderate or mild to severe periodontal diseases with gender, age, civil state and level of education or professional degree. It was not also find out a correlation with smocking, bruxism, onychophagy and dry mouth. It was found out that inflammatory periodontal disease is originated at the first relationships in the childhood and the schizoid anxiety which characterizes those first relationships keeps permeating on along all life of the patients. As the psychically defensive resources are less evoluted, the equilibrium is found through the illness. It was concluded that psychical dynamics is associated not only to periodontal diseases, but also to general health of those patients.